1991
DOI: 10.1113/jphysiol.1991.sp018726
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GABA systems in feedback regulation of glutamate‐and GABA‐mediated synaptic potentials in rat neostriatum.

Abstract: SUMMARY1. Neostriatal neurones were recorded intracellularly from a rat corticostriatal slice preparation. Depolarizing postsynaptic potentials (DPSPs) were evoked by either cortical or intrastriatal stimulation.2. Kynurenic acid (600 /tM), an antagonist of excitatory amino acids, reduced the cortically-evoked DPSPs by 88 % while the intrastriatally evoked potentials were reduced by 48 %. Bicuculline (100,tM) produced only a slight inhibition of the cortically evoked DPSPs (12 %), but clearly depressed intrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 44 publications
(53 reference statements)
8
78
2
Order By: Relevance
“…When the currents were evoked by hyperpolarizing command steps, there was no detectable time-dependent component. Some of these properties have been described previously both in vivo (Preston et al, 1979;Wilson and Groves, 1980;Calabresi et al, 1990c;Onn et al, 1994a;Xu, 1995) and in vitro (Kita et al, 1984;Calabresi et al, 1990bCalabresi et al, , 1991Calabresi et al, , 1995bJiang and North, 1991;Cepeda et al, 1994) and resemble those reported for intracellularly stained spiny striatal neurons (Preston et al, 1979;Cepeda et al, 1994;Onn et al, 1994b;Calabresi et al, 1995a).…”
Section: Physiological and Morphological Properties Of Spiny Neuronsmentioning
confidence: 64%
“…When the currents were evoked by hyperpolarizing command steps, there was no detectable time-dependent component. Some of these properties have been described previously both in vivo (Preston et al, 1979;Wilson and Groves, 1980;Calabresi et al, 1990c;Onn et al, 1994a;Xu, 1995) and in vitro (Kita et al, 1984;Calabresi et al, 1990bCalabresi et al, , 1991Calabresi et al, , 1995bJiang and North, 1991;Cepeda et al, 1994) and resemble those reported for intracellularly stained spiny striatal neurons (Preston et al, 1979;Cepeda et al, 1994;Onn et al, 1994b;Calabresi et al, 1995a).…”
Section: Physiological and Morphological Properties Of Spiny Neuronsmentioning
confidence: 64%
“…It has been reported that endogenous GABA controls its own release via GABA B autoreceptors. 25 Thus, high levels of GABAmimetic drugs reduce the release of endogenous GABA. Alternatively, it can be speculated that excessive activation of GABA A receptor may cause an overload of chloride ions into the neurons, leading to cell swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Many receptors participate in the presynaptic modulation of GABA transmission in the striatum, including the GABAB receptors (Calabresi et al, 1991). Thus, we investigated whether the abnormal control of GABA synapses observed in rewarded mice was specific only for CB1 receptors or also involved other presynaptic receptors.…”
Section: Effects Of Baclofen On Gaba Transmission After Running Wheelmentioning
confidence: 99%